2020
DOI: 10.1017/s1368980019003835
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean dietary pattern is associated with lower incidence of premenopausal breast cancer in the Seguimiento Universidad de Navarra (SUN) Project

Abstract: Objective: Due to the growing interest in the role of dietary patterns (DPs) on chronic diseases, we assessed the association between a posteriori identified DPs in the Seguimiento Universidad de Navarra (SUN) Project – a prospective cohort study in a Mediterranean country – and breast cancer (BC) risk. Design: DPs were ascertained through a principal component analysis based on 31 predefined food groups. BC cases were initially identified through self-report or, if deceased, from death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Alcohol predominately in the form of red wine represents the most controversial ´food group´ within the context of the associations of the MedDiet on cancer. Increased ROS synthesis, suppressed anti-tumour immune response as well as metabolization of ethanol into DNA-damaging acetaldehyde may all explain the positive association between alcohol intake and cancer [125,126]. The 3rd WCRF report indicated that there is a "convincing" grade of evidence for a positive association between alcohol intake and risk of upper aerodigestive, breast, colorectal or liver cancers, irrespective of the type of drink [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol predominately in the form of red wine represents the most controversial ´food group´ within the context of the associations of the MedDiet on cancer. Increased ROS synthesis, suppressed anti-tumour immune response as well as metabolization of ethanol into DNA-damaging acetaldehyde may all explain the positive association between alcohol intake and cancer [125,126]. The 3rd WCRF report indicated that there is a "convincing" grade of evidence for a positive association between alcohol intake and risk of upper aerodigestive, breast, colorectal or liver cancers, irrespective of the type of drink [10].…”
Section: Discussionmentioning
confidence: 99%
“…Differences between scores concerned mostly cut-off points for moderate alcohol consumption and a way of handling healthy fat intake. Five added studies derived MedDiet scores from principal component analysis [113,114,116,122,125].…”
Section: Definitions Of Mediterranean Dietmentioning
confidence: 99%
“…Studies on the effects of a Mediterranean diet, characterized by high intakes of fish, vegetables, beans, boiled potatoes, fruit, olives and vegetable oils, and a low intake of fruit juice, were carried out in the United States (n = 3), China (n = 2), Spain (n = 1), and Italy and Switzerland (n = 1), while studies of 'prudent' dietary patterns similar to a Mediterranean-style diet (34) have been carried out in China (n = 1), Spain (n = 1), and Poland (n = 2). A higher score for a Mediterranean diet was negatively related to BC in some studies (21-23, 28, 35, 36), especially after the menopause (37)(38)(39), while the Spanish study and two studies in the United States showed only a weak or no correlation (31,33,39). Prudent dietary patterns were associated with a lower risk of BC in one study (34), but had no observable effect on BC in the Spanish study (37)(38)(39).…”
Section: Dietary Patterns and The Risk Of Bcmentioning
confidence: 94%
“…A higher score for a Mediterranean diet was negatively related to BC in some studies (21-23, 28, 35, 36), especially after the menopause (37)(38)(39), while the Spanish study and two studies in the United States showed only a weak or no correlation (31,33,39). Prudent dietary patterns were associated with a lower risk of BC in one study (34), but had no observable effect on BC in the Spanish study (37)(38)(39).…”
Section: Dietary Patterns and The Risk Of Bcmentioning
confidence: 94%
See 1 more Smart Citation